2019
DOI: 10.1002/ppul.24241
|View full text |Cite
|
Sign up to set email alerts
|

Trends in epidemiology and outcomes of respiratory distress syndrome in the United States

Abstract: Background: The management practices of Respiratory Distress Syndrome (RDS) in the newborn have changed over time. We examine the trends in the epidemiology, resource utilization, and outcomes (mortality and bronchopulmonary dysplasia [BPD]) of RDS in preterm neonates ≤34 weeks gestational age (GA) in the United States.Methods: In this retrospective serial cross-sectional study, we used ICD-9 codes to classify preterm infants GA ≤34 weeks between 2003 and 2014 from the National Inpatient Sample as having RDS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 51 publications
0
31
0
3
Order By: Relevance
“…The NIS has been used to estimate population-level trends in numerous conditions. [15][16][17][18][19] Researchers and policymakers use the NIS to make national estimates of health care use, access, charges, quality, and outcomes. The NIS is released annually, which makes it an excellent database for longitudinal analysis.…”
Section: Methods Databasementioning
confidence: 99%
“…The NIS has been used to estimate population-level trends in numerous conditions. [15][16][17][18][19] Researchers and policymakers use the NIS to make national estimates of health care use, access, charges, quality, and outcomes. The NIS is released annually, which makes it an excellent database for longitudinal analysis.…”
Section: Methods Databasementioning
confidence: 99%
“…Studies indicate that the incidence of BPD has remained constant over the last few decades [6,7]. However, a recent study analyzing a large database of premature infants showed that the incidence of BPD has decreased over the last few years, with an increase in the use of non-invasive ventilation during the same period [8]. Mechanical ventilation with subsequent ventilator-induced lung injury (VILI) contributes to BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory distress syndrome (RDS) represents the main cause of respiratory failure in preterm neonates and is associated with an increasing burden of care [1]. Since RDS is caused by primary surfactant deficiency, the availability of exogenous surfactants allows an effective replacement therapy, which is recommended by current international guidelines, in neonates failing continuous positive airway pressure (CPAP) [2,3].…”
Section: Introductionmentioning
confidence: 99%